Influence of multi-stakeholder innovation platform approach on smallholder farmers marketing decisions - Mango, Nelson; Makate, Clifton; Lundy, Mark M.; Siziba, Shephard; Nyikahadzoi, Kefasi; Fatunbi, A.O. (African Journals Online, 2017)
One of the very numerous decisions that smallholder farmers face world wide relates to market participation in agricultural markets and, consequently choosing the appropriate marketing channel for their agricultural produce. Such decisions impact on their incomes and subsequently on their welfare. The objective of this study was to determine how a multi-stakeholder innovation platform approach influences pigeon pea (Cajanus Cajan L.) marketing decisions in smallholder farming in Malawi. The study relied on primary data collected from 115 households in Balaka District in Malawi during an impact survey done in November 2014. Results confirmed that the multi-stakeholder innovation platform approach improves decision making in pigeon pea marketing. Variables such as access to transport services and market information, improved extension, capacity building through farmer training, adoption of conservation agriculture and membership to farmer groups influenced marketing decisions.